Internalization Of Character Values Towards God Through Learning The Book Of Al-Akhlakul Lil Banat At The PP Mamba’ul Khoiriyatil Islamiyah Bangsalsari - Sayyidah Syaehotin (Prodi Pendidikan Agama Islam IAI Al-Qodiri Jember, 2023)
The purpose of this study was to describe the internalization of character values ​​towards God through learning the book Al-Akhlakul Lil Banat for female students at the MHI Islamic Boarding School in Bangsalsari Jember. The research method used is descriptive qualitative. The type of research used is field research (Field Research). Determination of research subjects using purposive sampling. Data collection techniques through observation, interviews and documentation. Data analysis using data reduction techniques, data presentation and drawing conclusions. Data validity through data triangulation and source triangulation. The results of his research show that the internalization of character values ​​to God through learning the Book of Al-Akhlaku Lil Banat for female students Ibtida'iyah at the MHI Bangsalsari Islamic Boarding School runs well and effectively. You can see the habits of the majority of female students who diligently pray in congregation, read the Qur'an.